Cognitive Impairment in Alzheimer's and Metabolic Diseases: A Catecholaminergic Hypothesis. (10th August 2022) - Guzmán-Ramos, Kioko; Osorio-Gómez, Daniel; Bermúdez-Rattoni, Federico
Highlights: Catecholamines modulate synaptic plasticity, learning and memory. Affectation of catecholaminergic nuclei is present in the early stages of Alzheimer's. Metabolic diseases cause neuroinflammation vulnerating catecholaminergic neurons. Catecholaminergic enzymes and receptors are affected in Alzheimer's. Catecholaminergic stimulation improves cognitive performance in Alzheimer's. Abstract: Catecholaminergic transmission plays an essential role in both physiological and pathological cognitive functions. Plastic changes subserving learning and memory processes are highly dependent on catecholaminergic activity, altering their function and impacting cognition. This review assesses changes in the dopaminergic and norepinephrine systems as part of the mechanisms underlying cognitive impairment in Alzheimer's disease as associated with metabolic dysfunctions such as type 2 diabetes, metabolic syndrome, and neuroinflammation and peripheral inflammation. Understanding the role of catecholaminergic systems in these conditions is relevant for identifying etiological factors that could advance diagnostic and therapeutic approaches for ameliorating cognitive alterations, disease onset, and progression.